IMPROVEMENT OF PROCESS AND METHODS OF TEACHING OF THE WATER-COLOUR PAINTING ON THE SPECIAL COURSE FROM TECHNOLOGY OF THE WATER-COLOUR PAINTING FOR THE STUDENTS OF THE FIRST COURSES OF KHUDOZHESTVENNO-GRAFYCHESKYKH FACULTIES OF PEDYNSTYTUTOV (Pedagogy of Higher and Secondary Education, 2022)
The improvement of process and methods of teaching of the water-colour painting, forming of knowledges, abilities and skills is examined in the article, as components of development of creative capabilities at students.